Innovation in public libraries learning from international library practice - Nicholson, Kirstie (Chandos information professional series, 2017)
"Innovation in Public Libraries examines the recent activities of successful and innovative libraries aroundthe world, presenting their initiatives in areas including library design, events and programmes, and creating customer experiences. It provides an overview of these libraries' successful experiences and identifies emerging global trends and themes. The author offers library practitioners guidance on how to pursue these trends in their own library environment, identifying achievable goals when planning programming, building and design improvements, and in developing customer interactions in order to emulate the experiences of international libraries." -- Provided by publisher.